Interleukin-18 and outcome after allogeneic stem cell transplantation: a retrospective cohort study - Radujković, Aleksandar; Müller-Tidow, Carsten; Dreger, Peter; Luft, Thomas; Schult, David (EBioMedicine, 2019)
Background - Interleukin-18 (IL-18) is involved in endothelial activation and dysfunction, and in the pathogenesis and severity of acute graft-versus-host disease (aGVHD). Its relevance for patient outcome after allogeneic stem cell transplantation (alloSCT) has not yet been comprehensively addressed. - Methods - Pre-transplant serum levels of free IL-18 were retrospectively assessed in a cohort of 589 patients (training cohort). Results were validated in 688 patients allografted in a different centre. The primary endpoint was overall survival (OS). Secondary endpoints included incidences of non-relapse mortality (NRM), relapse, and aGVHD. - Findings - In the training cohort, higher pre-transplant levels of free IL-18 were significantly associated with worse OS (hazard ratio [HR] per 1-log2 increase, 1.25, P=0.008) in multivariable models. This was due to a higher hazard of NRM (HR per 1-log2 increase, 1.39, P=0.001), rather than relapse. The associations of pre-transplant free IL-18 with higher NRM (HR per 1-log2 increase, 1.24, P=0.02) and shorter OS (HR per 1-log2 increase, 1.22, P=0.006) were confirmed in the validation cohort. In both cohorts, the correlations of higher pre-transplant free IL-18 serum levels with increased NRM and worse OS were mainly driven by fatal infectious complications. No associations with incidence of aGVHD were observed. - Interpretation - Higher pre-transplant levels of free IL-18 were associated with non-relapse and overall mortality after alloSCT. Our results may provide a rationale for prospective studies evaluating IL-18 status and inhibition of IL-18 activity in patients undergoing allografting.